Assessing the spatio-temporal impact of landuse landcover change on water yield dynamics of rapidly urbanizing Kathmandu valley watershed of Nepal - Suchana Acharya; Tomoharu Hori; Saroj Karki (Journal of Hydrology: Regional Studies, 2023)
Study Region: The Kathmandu valley watershed (KVW), capital region of Nepal, which is one of the rapidly urbanizing areas not only in Nepal but in South Asia. Study Focus: Haphazard landuse practice coupled with the lack of stringent landuse policies has put stress on already scarce resources like water, land, agriculture, etc. of the Kathmandu valley watershed (KVW). Given the underlying problem of unscientific landuse practice as a result of the rapid urbanization and the consequent water stress, this study has attempted to predict future landuse and hence comprehensively assess the spatio-temporal dynamics of water yield components in KVW from the past to the future. New Hydrological Insights for the region: A forecast of future land use indicates that nearly half of KVW will be covered by built-up areas by 2040. Land use changes are expected to significantly affect water yield components, particularly at the sub-basin level. Subbasin responses to land use and land cover (LULC) changes are most prominent for surface runoff, followed by groundwater flow, lateral flow, with the least impact on evapotranspiration (ET). Anticipated outcomes include a substantial 70% reduction in groundwater flow and a potential 200% increase in surface runoff in certain subbasins. These findings emphasize the urgent need to regulate land use practices and develop effective strategies to mitigate the adverse effects of uncontrolled urban expansion.